The effect of retail service quality on customer loyalty: the mediating role of customer satisfaction and trust - Haque, A. K. M. Ahasanul; Anwar, Naila; Moulan, Suharni; Abdullah, Kalthom; Tarofder, Arun Kumar (Hampstead Psychological Associates, 2020)
Intense competition within the retail industry made it vital to gain a clear understanding regarding the factors that affect customer loyalty towards retailers. It is utmost important for retailers to sustain their prominence through enhancing their base of loyal customers. Keeping this issue in mind, the present study aspires to investigate the factors that are responsible for building customer loyalty. Specically, it attempts to investigate the effect of retail service quality on customer loyalty through the mediating effects customer satisfaction and trust. erefore, a conceptual framework was constructed based on a review of prior studies. Aerwards, primary data were collected from Klang Valley, Malaysia, through the dissemination of self-administered questionnaires. Later on, SPSS and SEM were used for analysing the collected data. e results disclosed that retail service quality has a signicant effect of customer satisfaction, trust and customer loyalty. At the same time, the effect of retail service quality on customer loyalty is mediated by customer satisfaction and trust and trust mediates the effect of customer satisfaction on customer loyalty. e ndings of this study would aid retail managers in strategizing accordingly. It would also be an important addition to literature as well as help future researchers in furthering the current research.